2018
DOI: 10.1103/physrevphyseducres.14.010107
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between student attitudes and student learning

Abstract: Student attitudes, defined as the extent to which one holds expertlike beliefs about and approaches to physics, are a major research topic in physics education research. An implicit but rarely tested assumption underlying much of this research is that student attitudes play a significant part in student learning and performance. The current study directly tested this attitude-learning link by measuring the association between incoming attitudes (Colorado Learning Attitudes about Science Survey) and student lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 22 publications
1
26
0
2
Order By: Relevance
“…In many cases, students even know what physicists would say in the situations probed, but do not agree with them [1]. In addition to being important in themselves, attitudes that align with experts also somewhat predict learning [2][3][4][5]. Instruments such as Views about Science Survey (VASS) [6], Maryland Expectations about Science Survey (MPEX) [7], and the Colorado Learning Attitudes about Science Survey (CLASS) [8] have been developed to measure these attitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, students even know what physicists would say in the situations probed, but do not agree with them [1]. In addition to being important in themselves, attitudes that align with experts also somewhat predict learning [2][3][4][5]. Instruments such as Views about Science Survey (VASS) [6], Maryland Expectations about Science Survey (MPEX) [7], and the Colorado Learning Attitudes about Science Survey (CLASS) [8] have been developed to measure these attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Cahill et al [12] identified two categories for learning, using 25 statements, and proceeded to validate those with a confirmatory factor analysis (CFA). CLASS scores have been found to correlate weakly with learning outcomes [2,4,5] and experiencing high levels of challenge, interest, and skill at the same time (optimal learning moments) [13].…”
Section: Introductionmentioning
confidence: 99%
“…More targeted predictors focus on what knowledge and skills a student needs to succeed in a particular subject matter, such as the Force Concept Inventory (FCI). This inventory measures student understanding of force and related kinematics, and correlates with performance in introductory physics classes at both the high school and university levels (Hestenes, Wells, & Swackhamer, ; Savinainen & Scott, ; see also Cahill et al, , extending these findings to second semester introductory university courses, using the Brief Electricity and Magnetism Assessment [BEMA] as a predictor of course performance). However, while such measures can be extremely useful within specific classes, they are limited in their ability to generalize across subject areas.…”
mentioning
confidence: 99%
“…These expert-like beliefs are often seen as a desired learning goal as such. They have also been shown to correlate weakly with learning [28][29][30]. They also correlate with experiencing high levels of challenge, interest and skill at the same time (optimal learning moments) [31].…”
Section: Measuring Development Of Skill and Attitudesmentioning
confidence: 99%